CO + NH3 coupling denitration at low temperatures over manganese/activated carbon catalysts. Issue 53 (30th November 2022) - Luo, Liubin; Huang, Bangfu; Shi, Zhe; Wen, Zhenjing; Li, Wanjun; Zi, Gaoyong; Yang, Linjing
Abstract : The low-temperature CO + NH3 coupling denitration of the Mn/AC catalyst conforms to the L–H mechanism when the temperature is lower than 230 °C and the E–R mechanism when the temperature is higher than 230 °C. Abstract : To explore the mechanism of low-temperature carbon monoxide and ammonia (CO + NH3 ) coupling denitration of manganese/activated carbon (Mn/AC) catalysts, Mn/AC series catalysts were prepared using the impregnation method with AC activated by nitric acid as a precursor and manganese nitrate as a precursor. We characterized the surface morphology, pore structure, active component phase, functional group, and active component valence change law of the Mn/AC catalyst. The denitration rate order with different Mn loadings is 7Mn/AC > 9Mn/AC > 5Mn/AC. When the Mn loading was 7%, the catalyst's surface was smooth, with a good pore structure and uniform surface distribution of metal particles. These features increased the reacting gas's contact area, improving the denitration rate. The reason for this was oxygen chemisorption on the catalyst's surface. The Mn 4+ and the number of oxygen-containing functional groups on the catalyst surface increase after Mn loading increases; this provides more active sites for denitration and promotes the reaction's conversion to fast selective catalytic reduction. The low-temperature CO + NH3 coupling denitration of Mn/AC catalysts conforms to the Langmuir–Hinshelwood mechanism when the temperature is lower than 230 °C and the Eley–Rideal mechanism when the temperature is higher than 230 °C. The research results can provide new ideas for low-temperature flue gas denitration.